How to Build Strategic Communication: Speech Act Analysis on King Salman’s Speeches at the United Nations General Assembly - Reflinaldi, Reflinaldi; Faisol, Yufni; Hadi, Syofyan; Ilyas, Erizal (ppjbsip, 2024)
This research aims to explain the strategic communication used by King Salman at the United Nations General Assembly. A qualitative-explanatory design was applied to study King Salman's two speeches at the UN General Assembly in 2020 and 2021. Data collection was carried out through the stages of transcription, reading, printing, tabulation, coding, and classification. Meanwhile, data analysis that follows the framework of the form and function of illocutionary speech acts is carried out through the stages of description, selection, analysis and interpretation, and conclusion. The results show that there are four types of speech acts in King Salman's speech. The author found assertive speech acts in 47 data (49.5%), directive in 15 data (15.8%), commissive in 5 data (5.2%), and expressive in 28 data (29.5%). These forms of speech acts have various functions aimed at communicating the strategic dimensions of Saudi Arabian policy. Politically, the form and function of these speech acts seek to emphasize and improve Saudi Arabia's bargaining position in international geopolitical dynamics.